Multifunctionality of livestock in developing communities - Moyo, Siboniso; Swanepoel, F.J.C. (University of the Free State and CTA, 2010)
Livestock play multiple roles in the livelihoods of people in developing communities, especially the poor. They provide food and nutrition, work, economic and social status, and ensure environmental sustainability. With the livestock sector experiencing rapid change – mainly driven by the rapidly changing livestock production systems, demographics, environmental impacts, technologies, policies and institutions – this “multifunctionality of livestock” becomes an even more complex issue, intertwined with other research and development challenges. This chapter presents an overview of the multifunctionality of livestock, looking at the trends and drivers of livestock production in developing communities. Bringing this topic to the table is meant to draw the attention of the research and development community to the issues concerning the contribution of livestock to the social and economic progress of developing communities and thus attract both public and private sector investments in this sector.